Legal liability for health care-associated infections - Zieliński, Grzegorz; Kanecki, Krzysztof; Lewtak, Katarzyna (Family Medicine & Primary Care Review, 2022)
As defined by World Health Organization, a nosocomial infection or healthcare-associated infection is an infection occurring in a patient during the process of care in a hospital or other healthcare facility which was not present or incubating at the time of admission. This includes infections acquired in the healthcare facility but appearing after discharge, as well as occupational infections among healthcare workers of the facility. The Act of 5 December 2008 on preventing and combating infections and infectious diseases in humans defines healthcare-associated infection as “an infection that occurred in connection with the provision of health services, where the disease: did not occur at the time of providing health services during the incubation period or occurred after provision of health services, in a period not longer than the longest incubation period”. Healthcare providers and facilities owe a legal duty to ensure patient safety. In this article, important recent verdicts regarding nosocomial infections have been subject to legal analysis. They have been discussed in a broad context, including medical malpractice, guilt of doctors and healthcare facilities, the liability of doctors and healthcare facilities for damage caused during treatment and for violation of patient rights, causation and the burden of proof in trials and compensation for damage suffered.